Where are the Great Pyramids? - Hoobler, Dorothy; Hoobler, Thomas (Where is (Grosset & Dunlap), 2015)
In this informative account, Dorothy and Thomas Hoobler tell the story of the powerful pharaohs who commissioned the pyramids at Giza and offer a fascinating look at the culture of the afterlife in ancient Egypt, explaining exactly how mummies were made.